Optimization of high-temperature mechanical properties of aluminum alloys through exclusive precipitation of T-phase - Yijun Wu; Zhongwei Chen; Wei Le; Haolan Zhang; Weijiang Song; Zihan Yang (Journal of Materials Research and Technology)
An aluminum alloy with an actual composition of Al - 5.4 wt%Cu- 1 wt%Mn was cast and subjected to solution heat treatment for 1 h, 2 h, 4 h, 8 h, and 16 h to make the T-phase the sole strengthening phase. The microstructural evolution of the samples, especially the T-phase microstructure, was studied using transmission electron microscope (TEM) and scanning electron microscope (SEM) with electron backscatter diffraction (EBSD) attachment. The ImageJ software was utilized to statistically analyze T-phase content. Tensile tests were conducted to obtain mechanical property data, and high-temperature tensile tests were performed at 200 °C, 300 °C, and 400 °C to assess the high-temperature performance. Subsequently, the strengthening effect of the T-phase on the room-temperature and high-temperature mechanical properties of the aluminum alloy was quantitatively evaluated. The sample subjected to an 8 h solution treatment exhibited optimal strength and toughness. The yield strength was 147 MPa, and the tensile strength was 300 MPa. The yield strength contributed by the T-phase was 73 MPa. The tensile strength of the sample at 400 °C remained at 91 MPa. The T-phase contributes significantly to the mechanical properties of the aluminum alloy both at room temperature and at high temperatures.